Mathematical modelling for assessing fracture risk associated with osteoporosis - Monteiro, D. (2016)
Osteoporosis is a systemic skeletal disease, characterized by low boné mass and by changing the boné microstructure. According to the Portuguese Society of Osteoporosis and Metabolic Boné Diseases (SPODOM), this disease affects about 500,000 people in Portugal. This paper presents a study on the evaluation of the fractures risk due to boné demineralization through various risk factors. An optimization code is developed using a mathematical program for diagnosing the disease and to compare it with the diagnosis obtained from DEXA (Dual-energy X-ray absorptiometry) scans. The developed code is performed with Matlab method using genetic algorithms. Analysing the numerical resiilts it is possible to conclude that the program can predict the T-Score value based on previous DEXA exams and the patient life behaviour as physical exercise, drinking cofiFee, the smoking, previous disease and other factors.